Steroid metabolome in the umbilical cord: is it necessary to differentiate between arterial and venous blood - Pašková, Andrea; Pařízek, Antonín; Hill, Martin; Velíková, Marta; Vítků, Jana; Dušková, Michaela; Adamcová, Karolína; Koucký, Michal; Simjak, P; Černý, Andrej; Stárka, Luboslav (Physiological research, 2014)
Steroids are important markers in pregnancy. Although estimating their levels separately in umbilical arterial (UA) and venous blood (UV) enable more precise insights into the functioning fetoplacental unit compared to using mixed umbilical blood (UM), selective aspiration of UA and UV is technically more demanding than collecting UM. We measured the levels of 67 unconjugated steroids and steroid polar conjugates in UA and UV using GC-MS in 80 women giving birth within weeks 28 to 42 of gestation. The samples were sorted into three groups: women entering labor within weeks 28-32 (group A, n=19), weeks 33-37 (group B, n=19), and weeks 38-42 (group C, n=42) of gestation, respectively. The preterm labors were due to pathologies unrelated to steroid status. Most unconjugated steroids exhibited pronounced arteriovenous differences (AVD). The AVD were less distinct in more stable steroid conjugates. Most steroids positively correlate with gestational age, but unconjugated 5beta-reduced pregnanes show negative correlations, as do testosterone and androstenediol, substrates for the placental synthesis of estrogens. Tight correlations between steroids in UA and UV indicate that steroid measurements in UA, UV and UM can be accurately derived from each other, which is important for the diagnostics of steroid related diseases in newborns.
Keywords: Premature Birth; dospělí; předčasný porod; Female; novorozenec; Adult; mladý dospělý; ženské pohlaví; fetální krev; arteriae umbilicales; lidé; Infant, Newborn; těhotenství; Umbilical Cord; pupečník; Fetal Blood; metabolom; Young Adult; steroidy; Umbilical Veins; venae umbilicales; Metabolome; Pregnancy; Umbilical Arteries; Steroids; Humans